2020
DOI: 10.1364/oe.405655
|View full text |Cite
|
Sign up to set email alerts
|

Deterministic access of broadband frequency combs in microresonators using cnoidal waves in the soliton crystal limit

Abstract: We present a method to deterministically obtain broad bandwidth frequency combs in microresonators. These broadband frequency combs correspond to cnoidal waves in the limit when they can be considered soliton crystals or single solitons. The method relies on moving adiabatically through the (frequency detuning)×(pump amplitude) parameter space, while avoiding the chaotic regime. We consider in detail Si 3 N 4 microresonators with small or intermediate dimensions and an SiO 2 microresonator with large dimension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…In addition, although we do not take into account the thermally induced resonance shift which could be more significant than SPM, this red-shift effect could be approximated to be proportional to the intracavity power 33 . Therefore, the frequency shift is expressed as: where is the coefficient for the thermally induced shift which could be typically 5 to 10 times higher than 33 , 34 . We can use this approximation, at least qualitatively, to explain the thermally resulted resonance shift.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, although we do not take into account the thermally induced resonance shift which could be more significant than SPM, this red-shift effect could be approximated to be proportional to the intracavity power 33 . Therefore, the frequency shift is expressed as: where is the coefficient for the thermally induced shift which could be typically 5 to 10 times higher than 33 , 34 . We can use this approximation, at least qualitatively, to explain the thermally resulted resonance shift.…”
Section: Discussionmentioning
confidence: 99%
“…Although experiments suggest that solitoncomb structures are more likely to form on the red-detuned side of microresonator's pump resonance mode [22][23][24], it has been observed that in this spectral region thermo-optical effects can be so sizable that the soliton crystal stability is hampered [22][23][24]. To understand the influence of thermooptic effects on the dynamics of soliton-comb structures in Kerr optical microresonators, recently a theoretical model was proposed [25,26]. The model consists of the Lugiato-Lefever equation for the optical field propagation, with a term accounting for thermal detuning associated with the temperature variation in the microresonator cavity.…”
Section: Introductionmentioning
confidence: 99%
“…The temperature variation in this model is governed by the one-dimensional heat equation, in which the heat source term is proportional to the average power of the optical field within the microresonator cavity. In [25] the authors examined the influence of thermooptic effects on the stability of single-soliton and solitoncrystal structures in the ring-shaped optical Kerr microresonator, thus they established that in the absence of thermo-optic effects the stable regions for single solitons and soliton crystals partially overlap. However, when thermal effects are included via the thermal detuning term in the Lugiato-Lefever equation, the stability region of single solitons separates completely from the one of soliton crystal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 96 ] Versatile frequency detuning regimes for different Kerr comb behaviors have been experimentally and theoretically investigated through wavelength scanning involving thermal effects. [ 18–20,23,97–105 ] In particular, step‐like transitions are found to be associated with solitons and soliton crystals in Kerr microcavities. [ 18–20,23,106–108 ] For a fixed‐frequency pump laser, the detuning scanning to access soliton regimes can be realized by externally tuning the cavity temperature thus the relative wavelength detuning between the fixed‐wavelength laser and the resonance position.…”
Section: Introductionmentioning
confidence: 99%